2022
DOI: 10.1007/s10802-022-00905-5
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Factors in Within-Person Developmental Cascades of Externalising, Internalising and ADHD Symptoms in Childhood

Abstract: Previous studies have offered evidence for peer problems and academic achievement as mediators in developmental cascades from externalising to internalising problems, and from ADHD symptoms to both internalising and externalising problems. However, these mediators have not been found to fully account for these cascades, indicating that there may be additional mediators involved. This study investigated the role of harsh parenting and parental involvement alongside academic achievement and peer problems in medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…First, the results support prior research finding evidence for developmental cascades from conduct to emotional problems (Capaldi, 1992;Murray et al, 2020). Evidence for cascades in the other direction has been mixed (Carlson & Cantwell, 1980;Speyer et al, 2022), however, findings of the current study suggest that these cascades may be at play during middle childhood.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…First, the results support prior research finding evidence for developmental cascades from conduct to emotional problems (Capaldi, 1992;Murray et al, 2020). Evidence for cascades in the other direction has been mixed (Carlson & Cantwell, 1980;Speyer et al, 2022), however, findings of the current study suggest that these cascades may be at play during middle childhood.…”
Section: Discussionsupporting
confidence: 83%
“…Studies have found evidence for developmental cascades from externalising problems to internalising problems (e.g., Murray et al, 2020). However, few studies have tested such cascades within a framework that allows for an appropriate disaggregation of within-person effects (for an example, see Speyer et al, 2022), and no studies have investigated whether the strength of such cascade effects may be affected by continuous moderating factors. In line with a risk-protective model (Rutter, 1979), factors such as cognitive abilities or peer problems may buffer or increase an individual's risk for the development of co-occurring mental health problems.…”
Section: Empirical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Some early studies have noted no significant predictive effects (also known as cascading effects [ 20 ]) between internalising and externalising mental health in children or adolescents [ 22 24 ]. In contrast, other evidence has come to light indicating a unidirectional predictive effect [ 10 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the above studies on the interplay between internalising and externalising mental health symptoms have adopted a state-trait perspective [ 10 , 24 , 26 ], recognising that childhood internalising and externalising mental health symptoms are characterised by both stability and change over time. Hence, it is important to distinguish between inter-individual (also known as between-child) associations from intra-individual (also known as within-child) associations between and within the domains of internalising and externalising symptoms.…”
Section: Introductionmentioning
confidence: 99%